O grau de sofisticaç\~ao relativa das exportaç\~oes brasileiras: 1996-2007 - Honorio Kume; Guida Piani; Pedro Miranda (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper analyzes the performance and the specialization pattern of Brazil's exports compared to a selected group in emerging countries - China, South Korea, India, Mexico and Russia - in 1996-2007, based on the sophistication level of exported goods according to the methodology of Hausmann, Hwang and Rodrik (2007). The results show that China and South Korea improve their position in market more sophisticated goods. The level of sophistication of Brazilian exports increased in the period 1996-2000 and remained approximately constant thereafter. In this group of countries, deserves prominence the South Korea that more than tripled the level of sophistication, while Brazil did not become more specialized in exports of more sophisticated products as did China, South Korea and India.
Keywords: F14; 330; Brazilian exports; relative sophistication; Export; Brasilien; Schwellenländer